Systematic Literature Review Cost Efficiency with Fuel and using Onshore Power Supply - Febriyanti Febriyanti; Muhammad Thamrin; Lira Agusinta; Yosi Pahala (Green Publisher, 2025)
The shipping world has now entered the zeroemission era by the IMO where members apply zero emission at the Port which aims to create a Green Port. In Indonesia, regulations on the implementation of OPS installations at the Port are contained in the Decree of the Minister of Transportation of the Republic of Indonesia number 8 of 2023 concerning the Determination of Climate Change Mitigation Actions in the Transportation Sector for Achieving the Target Contribution of the Utilization of New Renewable Energy (EBT) where the form of mitigation action is a. Implementation of OPS at the Port b. Making Regulations and Monitoring OPS Implementation so that the success indicator is reduced ship fuel consumption while docked at the Port. The coding used in this research is Green Port, Cost and Enviromental Benefit, Cost Efficiency, Renewable Energy, Saving Cost of the Ship Maintenance, Saving the cost of Fuel.